Influence of geometric parameters on the restraint of guardrail posts by asphalt mow strips. Issue 1 (2nd January 2017) - Lee, Seo-Hun; Bakhtiary, Esmaeel; Scott, David W.; Stewart, Lauren K.; White, Donald W.
Abstract: Asphalt pavement mow strips, used as a vegetation barrier in guardrail systems, have typically been regarded as a rigid layer in roadside design. However, geometric parameters of the mow strip such as thickness and rear distance behind the post have a significant impact on the amount of restraint the asphalt layer provides to resist translation and rotation by the posts. In this paper, a standard steel guardrail post designed with a range of asphalt mow strip dimensions is evaluated. A survey of the use of asphalt pavement mow strips in the United States was undertaken to determine an initial set of mow strip designs for investigation. Static tests were performed based on these designs, and finite element models were calibrated using the test data and parallel material characterization experiments. Utilizing the calibrated finite element model, simulations were performed on a wide variety of asphalt mow strip designs. Simulation and experimental results were correlated to develop a set of quantitative performance criteria. These criteria were used to assess the amount of ground-level restraint on a guardrail post caused by a given asphalt mow strip design in comparison with the existing design recommended by American Association of State Highway and Transportation Officials.